Aerogel applications in textile materials - Karabulut, Cengiz; Başyiğit, Zeynep Ömeroğulları; Ünsal, Cem; Toprakkaya Kut, Y. Dilek (Wydawnictwo Politechniki Łódzkiej, 2022)
The production of materials that will provide the high-performance properties required by today's technology is important for many sectors. Apart from meeting clothing and shelter needs, there is a direct or indirect rising need for the use of advanced textile materials in many different areas. Compared to the conventional materials, aerogel materials attract attention due to their ultra-lightweight structure with superior properties such as high specific surface area, high porosity, low density, low dielectric constant, excellent sound, and heat insulation. In addition, for the functional use of aerogel materials in the industry, mechanical properties such as modulus of elasticity, tensile-compressive strength, shear modulus, and impact strength are also important. When the literature on aerogel since the early 1930s is examined, it is seen that the studies mostly focused on application areas and more economical production ways. Although the most established application of aerogels in textiles is to improve thermal insulation, it is seen that they are also used in water repellency, air and water permeability, acoustic insulation, prevention of electromagnetic radiation, protection against chemicals, flame retardancy and treatment of textile process wastes. In this article, besides general information about aerogel, current aerogel application examples in textile materials are also included.
Keywords: aerogel; textile; organic; inorganic; functional materials; aerożel; tekstylia; organiczny; nieorganiczny; materiały funkcjonalne